Lignin-based 3D scaffolds for bone tissue regeneration applications - Barroso, Adriana Sofia da Silva (2022)
The bone is a connective, vascularized, and mineralized tissue that participates in the protection of organs, support and locomotion of the human body, maintenance of homeostasis, and in hematopoiesis. However, throughout the lifetime, bone defects may arise caused by trauma (mechanical fractures), disease, and/or aging, which when too extensive compromise the ability of the bone to self-regenerate. In these circumstances, lesions can be treated through different types of grafts, such as auto-, allo-, or xenografts. However, these approaches have some disadvantages, such as limited availability, the formation of new lesions, and the possibility of rejection. Thus, new methodologies have been developed, permanent or temporary, to support and accelerate the process of bone regeneration. Particularly, rapid prototyping techniques using composite materials (consisting of ceramics and polymers) have been showing the ability to allow the rapid development of customized 3D structures with osteoinductive and osteoconductive properties. In order to reinforce the mechanical and osteogenic properties of these 3D structures, herein, a new 3D scaffold was produced through the layer-by-layer deposition of a tricalcium phosphate (TCP), sodium alginate (SA), and lignin (LG) mixture using the Fab@Home 3D-Plotter. The composition of the 3D printed mixture, i.e., inorganic and organic phases, mimicked the natural composition of the bone matrix. Three different TCP/LG/SA scaffolds were produced by varying the LG/SA ratio (i.e., 1:3, 1:2, and 1:1) and compared with the TCP/SA scaffolds. The results demonstrated that the LG inclusion improved the mechanical resistance of the scaffolds, particularly in the 1:2 formulation, and improved the water contact angle (WCA). Furthermore, the TCP/LG/SA scaffolds presented high biocompatibility during the 7 days of study and supported the adhesion and proliferation of hOB cells. Additionally, no significant differences were observed in the calcium deposition on TCP/LG/SA scaffolds, when compared to the TCP/SA counterparts. In conclusion, the results support the application of TCP/LG/SA scaffolds in bone regeneration, originating stronger structures with more suitable environments for cell adhesion and proliferation.